2022
DOI: 10.3390/ijerph19020854
|View full text |Cite
|
Sign up to set email alerts
|

Mental, Physical and Socio-Economic Status of Adults Living in Spain during the Late Stages of the State of Emergency Caused by COVID-19

Abstract: Research has shown that the confinement measures implemented to curb the spread of COVID-19 can have negative effects on people’s lives at multiple levels. The objective of this cross-sectional study was to better understand the mental, physical, and socio-economic status of adults living in Spain during the late stages of the state of emergency caused by COVID-19. Five hundred and forty-four individuals responded to an online survey between 3 June and 30 July 2020. They were asked to report data about their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
4
6
0
Order By: Relevance
“…Our study employs ordinary least squares to investigate the relationship between income and individual mental health nationwide and to provide empirical evidence for the effect of income on individual mental health. The results of this paper were consistent with previous studies [ 7 ]. However, most studies used non-probability samples.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our study employs ordinary least squares to investigate the relationship between income and individual mental health nationwide and to provide empirical evidence for the effect of income on individual mental health. The results of this paper were consistent with previous studies [ 7 ]. However, most studies used non-probability samples.…”
Section: Discussionsupporting
confidence: 94%
“…For example, Ferrara et al [ 6 ] reported that the COVID-19 disease and the restrictive government measures harmed the mental health of individuals around the world, causing fear, frustration, anger and a long list of complex negative emotions. This result was also confirmed by Sánchez et al [ 7 , 8 , 9 , 10 ]. McAlearney et al [ 11 ] studied the mental health status of first responders (including police, firefighters, and emergency medical services) and their influencing factors during the pandemic.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…For example, Xiong et al (2022) reported that the COVID-19 pandemic had caused high levels of anxiety, depression, and stress in many different countries, which may have a negative impact on individual’s mental health. This result was also confirmed by Sánchez et al ( Huremović, 2019 ; Cao et al, 2020 ; Galli et al, 2022 ; Sánchez-Rodríguez et al, 2022 ). McAlearney et al (2022) studied the mental health status of first responders (including police, firefighters, and emergency medical services) and their influencing factors during the pandemic, and many similar studies have been conducted in the literature ( Cohen Veterans Network, 2020 ; Stogner et al, 2020 ; Hendrickson et al, 2022 ).…”
Section: Introductionsupporting
confidence: 84%
“…In this study, only data from 434 potential participants that provided complete information were included. Although two articles have been published using data from this survey [ 16 , 17 ], neither of them addressed the question that is the focus of the current study.…”
Section: Methodsmentioning
confidence: 99%